SUPERVISI AKADEMIK KEPALA SEKOLAH DI SEKOLAH DASAR BERAKREDITASI A - Sutinah Sutinah (Manajer Pendididikan, 2015)
The purpose of this research was to describe the academic supervision in elementary school principals 1 in Bengkulu City.The method of this research used qualitative descriptive .The collecting data used interview,observation,and cumentation.The result of this research showed that academic supervision principals in elementary schools accredited in Bengkulu City of Elementary School 1 was run in accordance with applicable regulations. The Principals more emphasized on performance appraisal and professional development of teachers associated with the ability of teachers in planning learning programs, learning procedures, interpersonal teachers and students , and increase ability (abilities and skills)of teachers in generally.Keywords: academic supervision , principal